2022
DOI: 10.1371/journal.pbio.3001481
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary plasticity and functional versatility of CRISPR systems

Abstract: The principal biological function of bacterial and archaeal CRISPR systems is RNA-guided adaptive immunity against viruses and other mobile genetic elements (MGEs). These systems show remarkable evolutionary plasticity and functional versatility at multiple levels, including both the defense mechanisms that lead to direct, specific elimination of the target DNA or RNA and those that cause programmed cell death (PCD) or induction of dormancy. This flexibility is also evident in the recruitment of CRISPR systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 82 publications
(125 reference statements)
0
44
0
Order By: Relevance
“…In contrast, Cas12 proteins only contain the RuvC-like nuclease domain, similarly to TnpB. The ancestral status of the transposon-encoded nucleases with respect to the CRISPR effectors is supported by general considerations, namely, the small size and compactness of IscB and TnpB, and the simple organization of the transposons themselves compared to the CRISPR-Cas systems ( Koonin and Makarova, 2022 ). More importantly in the phylogenetic trees of the two nuclease families, Cas9 forms a single clade embedded amongst transposon-encoded IscBs ( Altae-Tran et al, 2021 ), whereas different Cas12 variants comprise several such clades in the TnpB ( Faure et al, 2019 ).…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Cas12 proteins only contain the RuvC-like nuclease domain, similarly to TnpB. The ancestral status of the transposon-encoded nucleases with respect to the CRISPR effectors is supported by general considerations, namely, the small size and compactness of IscB and TnpB, and the simple organization of the transposons themselves compared to the CRISPR-Cas systems ( Koonin and Makarova, 2022 ). More importantly in the phylogenetic trees of the two nuclease families, Cas9 forms a single clade embedded amongst transposon-encoded IscBs ( Altae-Tran et al, 2021 ), whereas different Cas12 variants comprise several such clades in the TnpB ( Faure et al, 2019 ).…”
Section: Mainmentioning
confidence: 99%
“…Exaptation refers to the recruitment, driven by natural selection, of a biological entity for a new role unrelated to the original one with respect to the biological function, while exploiting the mechanistic features of the recruited entity ( Gould and Vrba, 1982 ; Gould, 1997 ). We use this term instead of the more common “domestication” to emphasize the functional shifts that occur upon recruitment of MGEs or their components for cellular functions ( Koonin and Krupovic, 2018 ; Koonin and Makarova, 2022 ). For example, a nuclease originally involved in transposition of a distinct variety of IS200/IS605-like transposons evolved into Cas9, the effector of type II CRISPR-Cas adaptive immunity ( Kapitonov et al, 2016 ; Altae-Tran et al, 2021 ), whereas the transposase of another type of transposons gave rise to Cas1, the integrase involved in spacer acquisition by CRISPR-Cas systems ( Krupovic et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…This constitutes a null model of CRISPR immunity that provides a useful comparison point for both more accurate mechanistic models and experimental data. CRISPR is one of many other bacterial antiviral defense systems [91], and within the CRISPR world, CRISPR systems are highly evolutionarily diverse and there are many known differences in function and effect between CRISPR systems of different bacterial species [92, 93, 94, 95]. Experiments typically study a particular CRISPR system, and it is unclear which revealed mechanisms are specific to that system or are a more general property of CRISPR systems.…”
Section: Discussionmentioning
confidence: 99%
“…Although all CRISPR-Cas systems follow this general pathway, they exhibit striking diversity in the composition of their effector complexes and mechanisms of action. Accordingly, they have been divided into two classes, six Types (I-VI), and over 30 subtypes (Makarova, Wolf, et al 2020; Koonin and Makarova 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Type III CRISPR-Cas systems are the most closely related to the ancestral system from which all Class I systems have evolved and are arguably the most complex (Mohanraju et al 2016; Koonin and Makarova 2022). Type III systems typically utilize multi-subunit effector complexes which recognize foreign RNA and coordinate a sophisticated immune response that results in the destruction of the invading RNA and DNA.…”
Section: Introductionmentioning
confidence: 99%